2008
DOI: 10.1186/1471-2407-8-89
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific incidence and temporal trends in solid tumours in young people from Northern England, 1968–2005

Abstract: Background: This study examined sex-specific patterns and temporal trends in the incidence of solid tumours in the Northern Region of England from 1968 to 2005. This updates earlier analyses from the region where sex was not considered in depth. Sex-specific analyses were carried out to determine whether sex differences might provide clues to aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
4
19
1
2
Order By: Relevance
“…31 A study in England reported an increased melanoma incidence trend for female 15-to 24-year-olds from 1968 through 2005. 29,32 The increasing melanoma incidence, especially in 15-to 19-year-olds, is consistent with our analyses. For 0-to 9-year-olds, melanoma incidence was fairly stable from 1973 through 2009.…”
Section: Discussionsupporting
confidence: 80%
“…31 A study in England reported an increased melanoma incidence trend for female 15-to 24-year-olds from 1968 through 2005. 29,32 The increasing melanoma incidence, especially in 15-to 19-year-olds, is consistent with our analyses. For 0-to 9-year-olds, melanoma incidence was fairly stable from 1973 through 2009.…”
Section: Discussionsupporting
confidence: 80%
“…Several recently published studies have reported that bone tumour incidence remains stable over time in spite of an overall increase in cases of childhood cancer (McNally et al, 2001;Stiller et al, 2006a;Magnanti et al, 2008), with one specifically reporting stable incidence of Ewing sarcoma for the time period 1973-2004(Esiashvili et al, 2008. Our observed decrease in the incidence of Ewing sarcoma remains unexplained.…”
Section: Discussioncontrasting
confidence: 36%
“…The majority of these tumours are osteosarcoma or Ewing sarcoma (Stiller et al, 2006a), in the United Kingdom 54% being osteosarcoma, 39% Ewing sarcoma, 2% chondrosarcoma and 5% other types (Stiller, 2007). Worldwide, trends in incidence rates for childhood bone tumours have remained constant (McNally et al, 2001;Stiller et al, 2006a;Magnanti et al, 2008), although a few studies have reported increases (Ajiki et al, 1994;Gurney et al, 1996). The substantial improvement in survival over the past 40 years (Arndt et al, 2007) has been attributed to chemotherapy (Stiller et al, 2006a).…”
mentioning
confidence: 99%
“…Other studies of patients aged 15-24 years, using the same database from the northern region of England, have identified a male-specific increase in the incidence of non-melanotic skin cancer, a male-specific decrease for lymphomas and female-specific increases for osteosarcoma, thyroid cancer and melanoma [25,26]. Survival has improved for most other cancers and for both males and females [27].…”
Section: Discussionmentioning
confidence: 90%